Modernizing Multilateralism : Learning from Military History - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank Group, spoke on the theme of modernizing multilateralism and learning from military history. As the world moves toward multiple poles of growth, the multilateral institutions will need to play a role in connecting developed and developing countries to work cooperatively. The World Bank is a facilitator of such cooperation. The results matter. A focus on outcomes may seem obvious, but assessments of public institutions are often driven by intellectual debates, political positioning, and current ideological fashions. We need thought plus action.